Principal Leadership in Improving The Quality of Educators in The Era of Revalution 4.0 - Ridho, Muhammad Rasyid (IAIN Syekh Nurjati Cirebon, 2022)
Industry Revolution 4.0Â happening today certainly has a huge impact on the educational leadership of school leaders, of course this must be addressed wisely by policy makers in the educational environment. Principals in the 21st century must of course be equipped with professional leadership so that it has an impact on improving the quality of educators. This study uses a descriptive qualitative approach with the type of literature study, data obtained through various references to national, international journals and research results that have relevance to what the author did. The results of this study indicate that the leadership of school principals in the era of the Industrial Revolution 4.0 must of course be professional and able to read the changes that occur because of the ideal leadership, namely leadership that follows technological developments. In addition, school principals also play a role in improving the quality of educators, there are several things that must be done by school principals in improving the quality of educators, namely the use of information technology, training, mentoring and guidance, discipline development and continuous supervision.Keywords: Principal Leadership, Educator Quality, Industrial Revolution 4.0Revolusi Industri 4.0 yang terjadi saat ini tentu memiliki dampak yang sangat besar terhadap kepemimpinan pendidikan para pemimpin sekolah, tentunya hal ini harus disikapi dengan bijak oleh para pembuat kebijakan di lingkungan pendidikan. Kepala sekolah di abad ke-21 tentunya harus dibekali dengan kepemimpinan yang profesional sehingga berdampak pada peningkatan kualitas pendidik. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan jenis studi kepustakaan, data yang diperoleh melalui berbagai referensi jurnal nasional, internasional dan hasil penelitian yang memiliki relevansi dengan apa yang penulis lakukan. Hasil penelitian ini menunjukkan bahwa kepemimpinan kepala sekolah di era Revolusi Industri 4.0 tentunya harus profesional dan mampu membaca perubahan yang terjadi karena kepemimpinan yang ideal, yaitu kepemimpinan yang mengikuti perkembangan teknologi. Selain itu, Kepala Sekolah juga berperan dalam meningkatkan kualitas pendidik, ada beberapa hal yang harus dilakukan oleh Kepala Sekolah dalam meningkatkan kualitas pendidik, yaitu penggunaan teknologi informasi, pelatihan, pendampingan dan bimbingan, pengembangan disiplin dan pengawasan terus menerus.Kata kunci: Kepemimpinan Kepala Sekolah,Â Mutu Pendidik, Revolusi Industri 4.0